EFFECT OF CLEARANCE ON THE HEIGHT OF (BURR) ON ARM REAR BRAKE TYPE 45P AT PT. XYZ KARAWANG - Sumardi Sumardi; Kardiman Kardiman; Farradina Choria Suci (UNIVERSITAS SRIWIJAYA, 2021)
Arm rear break is one component of vehicle spare parts found on motorcycles. This component is made using a forming process, where one of the parameters that affects the failure is the clearance value. Therefore, the purpose of this study was to determine the effect of clearance on the burr height of the 45P Arm Rear Break. The arm rear break is made of sheet metal plate material with a thickness of 2.6 mm through the forming process and variations in clearance numbers of 4%, 5% and 6%. For the punching process, a 12 mm diameter punch knife was used. The result of this research is that the highest bar value is produced by 6% clearance of 0.29 mm, then 5% clearance of 0.23 mm and 4% clearance of 0.17 mm. Keywords : Sheet metal, forming, arm rear brake, clearance, burr